2015
DOI: 10.1037/a0038100
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the Ten-Item Perceived Stress Scale.

Abstract: Although the 10-item Perceived Stress Scale (PSS-10) is a popular measure, a review of the literature reveals 3 significant gaps: (a) There is some debate as to whether a 1- or a 2-factor model best describes the relationships among the PSS-10 items, (b) little information is available on the performance of the items on the scale, and (c) it is unclear whether PSS-10 scores are subject to gender bias. These gaps were addressed in this study using a sample of 1,236 adults from the National Survey of Midlife Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
300
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(323 citation statements)
references
References 46 publications
19
300
1
3
Order By: Relevance
“…This measurement tool has been validated and is often used as an instrument to estimate everyday life stress [31]. Because the outcome measure for dyspepsia is based on collected prescriptions, it cannot be confirmed that they actually had dyspepsia, but it is likely that they had symptoms because a physician prescribed the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measurement tool has been validated and is often used as an instrument to estimate everyday life stress [31]. Because the outcome measure for dyspepsia is based on collected prescriptions, it cannot be confirmed that they actually had dyspepsia, but it is likely that they had symptoms because a physician prescribed the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The PSS-10 consisted of 10 items on predictability, controllability, and life overload, as perceived by the individual during the last month [31,32]. Each question had five possible answers scaled from never to very often.…”
Section: Exposurementioning
confidence: 99%
“…The questionnaire for the study was designed by Taylor JM, in precedent research on "Psychometric analysis of the Ten-Item Perceived Stress Scale" [7]. The subject was Scores ranging from 0∼13 would be considered low stress (2 stage), scores ranging from 14∼26 would be considered moderate stress (3 stage), and scores ranging from 27∼40…”
Section: Perceived Stress Scalementioning
confidence: 99%
“…The internal consistency of the PSS has been established, and the test-retest reliability of the PSS is identified as six weeks with few studies confirming test-retest timeframes (Lee, 2012). The PSS has been recommended as a tool for identifying individuals at risk of developing psychiatric conditions, and the 10-item scale is the most frequently used version of the PSS in educational and psychology research (Taylor, 2014).…”
Section: Instrumentsmentioning
confidence: 99%